Design and analysis of QCA adder circuits for efficient computation - J, Jency Rubia (2021)
QCA technology is considered a viable alternative for CMOS technology since it solves most of the CMOS implications. The Quantum dot Cellular Automata is a computer software program that relates a discrete dynamical system with quantum mechanics. Quantum mechanics is a kind of physics about subatomic particles and which has many interesting properties. The QCA offers very great switching speed and consumes power dissipation extensively. The logic circuits play an essential role in the branch of computer arithmetic. In this paper, the adder circuits have been designed using the novel transistor-free technology called QCA. In addition to that, the planned work has been investigated with CMOS technology. The proposed work is simulated and synthesized by QCA designer suit 2.0.3.